Part 1: Creating Scientist-Citizens through a Writing Minor - Melissa Carrion; Ed Nagelhout (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
Part 1: Creating Scientist-Citizens through a Writing Minor